Cyclical Europeanisation during the COVID-19 crisis - Immonen, Waltteri (Routledge, 2025)
Utilising expert interviews, the article examines how different but overlapping logics of action guided the policies of the EU and its member states in the first year and a half of the Covid pandemic. We see three distinct logics – selfishness, emulation and coordination – taking shape, which together form a framework of cyclical Europeanisation. Efforts to cope with the pandemic made tensions between the Commission and its self-interested member states apparent. However, the member states were simultaneously able to learn from each other and thus emulate policy practices under conditions of uncertainty. Hence, regardless of the problems incurred, the ability to revert the tensions between the different logics of action and combine them pragmatically has reinforced some sense of Europeanisation within the European polity. External shocks intensify the cycles through which Europeanisation evolves and materialises, and bring to light the EU’s ability to act and react, improvise and adapt.